Against the sky [large type] - Martin, Kat (Martin, Kat. Brodies of Alaska., 2015)
After one reckless, passionate night in Las Vegas with Detective Nick Brodie, Samantha Hollis decides to follow him to Alaska where she becomes entangled in a web of murder, kidnapping and danger in which she discovers the depths he will go to find the truth.